2018
DOI: 10.1007/s12020-018-1559-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of l-carnitine supplementation on serum leptin concentrations: a systematic review and meta-analysis of randomized controlled trials

Abstract: L-carnitine consumption does not reduce serum leptin significantly. However, a significant effect on leptin was observed in diabetic patients and patients who received doses more than 3 mg per day in the course of <12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…The serum level of leptin is proportional to the body fat mass. Thus, the level of leptin drops by decrease of the adipose tissue mass [29]. Moreover, obesity is a chronic in ammatory disease that causes lipid peroxidation by abnormal production of pro-in ammatory factors such as IL-6 and CRP as well as release of free fatty acids from adipose tissue [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum level of leptin is proportional to the body fat mass. Thus, the level of leptin drops by decrease of the adipose tissue mass [29]. Moreover, obesity is a chronic in ammatory disease that causes lipid peroxidation by abnormal production of pro-in ammatory factors such as IL-6 and CRP as well as release of free fatty acids from adipose tissue [4].…”
Section: Discussionmentioning
confidence: 99%
“…Animal study also demonstrated that L-carnitine can reduce KOA symptoms [12]. Earlier studies showed that L-carnitine can signi cantly reduce CRP and MDA in coronary [29,30] and hemodialysis patients [31]. Meta-analysis also showed that L-carnitine supplementation signi cantly reduced the levels of CRP [13], cholesterol and lowdensity lipoprotein cholesterol (LDL-C) in diabetic patients [14].…”
Section: Introductionmentioning
confidence: 91%
“…Karnitin kaynaklarının tükendiği hemodiyaliz hastalarında takviye olarak kullanımı yaygındır. L-Karnitinin çeşitli mekanizmalarla vücut ağırlığını azalttığı ve hipotalamusa doğrudan etki ederek iştahı ve besin alımını baskıladığı bildirilmektedir (Nazary-Vannani, 2018). Yapılan bir meta-analize göre Lkarnitin desteğinin, vücut yağ oranına etki etmese de vücut ağırlığı, BKİ, yağ kütlesi ve bel çevresini önemli ölçüde azalttığı sonucuna varmıştır (Askarpour, 2020).…”
Section: Gurmarunclassified
“…Carnitine regulates lipid profiles by stimulating lipolysis and βoxidation, 5 as a result, lowering triglyceride, total cholesterol, and low-density lipoprotein cholestenone, 6 whereas has little effect on the Apo B100, Apo A1, and leptin. 7,8 Therefore, via the capability of converting fatty acid and antioxidative stress, carnitine has been used as pharmacological aid in many diseases including obesity, diabetes mellitus, and depression. [9][10][11][12][13][14] Currently, carnitine has also been used to improve insulin resistance (IR) and lipid metabolic disorders in women with PCOS, aiming to provide benefits for infertility.…”
Section: Introductionmentioning
confidence: 99%